2022
DOI: 10.1111/jop.13274
|View full text |Cite
|
Sign up to set email alerts
|

Central giant cell granulomas of the jaws stromal cells harbour mutations and have osteogenic differentiation capacity, in vivo and in vitro

Abstract: Background: Central giant cell granulomas (CGCG) of the jaws are osteolytic lesions that may behave aggressively and respond poorly to surgery. Microscopically, in addition to giant cells, there is a mononuclear cell population composed of macrophage/ monocytic cells and spindle-shaped cells of mesenchymal origin. Seventy two percent of these tumours harbour mutually exclusive TRPV4, KRAS and FGFR1 mutations. We aimed to assess the mutational status of mononuclear and giant cells and the osteogenic potential o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 29 publications
2
3
0
Order By: Relevance
“…Gomes and colleagues demonstrated that sporadic CGCL of the jaws do not share the H3F3A pGly34Trp or p.Gly34Leu mutations reported in GCT of long bones. These ndings appear to add to the body of evidence that the CGCL of the gnathic bone is distinct and separate from the extragnathic GCT [19].…”
Section: Discussionsupporting
confidence: 55%
“…Gomes and colleagues demonstrated that sporadic CGCL of the jaws do not share the H3F3A pGly34Trp or p.Gly34Leu mutations reported in GCT of long bones. These ndings appear to add to the body of evidence that the CGCL of the gnathic bone is distinct and separate from the extragnathic GCT [19].…”
Section: Discussionsupporting
confidence: 55%
“…Chrcanovic et al demonstrated that sporadic CGCG of the jaws do not share the H3F3A pGly34Trp or p.Gly34Leu mutations reported in GCT in long bones. These ndings appear to add to the body of evidence that the CGCG of the gnathic bone is distinct and separate from the extragnathic GCT [19,20].…”
Section: Discussionsupporting
confidence: 53%
“…[14][15][16][17][18] Giant cell lesions of the jaws may rarely occur in the setting of RASopathy syndromes such as Noonan syndrome or neuro bromatosis. Recently, CGCG have been recognized as benign neoplasms characterized by Ras/MAPK signaling pathway mutations [19].…”
Section: Discussionmentioning
confidence: 99%
“…Sporadic GCG is characterised by somatic, heterozygous, gain‐of‐function KRAS , FGFR1 , and TRPV4 mutations, which were detected in 72% (42/58) of cases [ 8 ]; specifically, KRAS p.G12D/A, p.G13D, p.A146V/P, p.V14L, p.L19F, and p.G10E mutations, FGFR1 p.N330I and p.C381R, and TRPV4 p.M713V/I mutations, with the latter exclusively detected in central lesions [ 8 ]. Such mutations are restricted to the mononuclear cells of the lesions [ 34 ], and converge to activation of MAPK/ERK signalling pathway [ 8 ]. No other pathogenic recurrent mutation could be identified in the remaining 30% of ‘triple wild‐type’ cases [ 8 ].…”
Section: Discussionmentioning
confidence: 99%